Cryptocurrency regulation and market volatility: analyzing the impact of global policy interventions on financial stability - Sunita Dasman; Santorry Santorry; Halim Tjiwidjaja; Dhany Anggoro Hastomo; Yani Dahliani (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Cryptocurrencies, as a rapidly growing asset class, have raised concerns regarding financial stability due to their high market volatility. This study investigates the impact of global regulatory interventions on cryptocurrency market volatility and financial stability through a mixed-methods design, combining both quantitative and qualitative approaches. The primary objective is to assess how regulatory policies in key jurisdictions, such as the United States, China, and the European Union, influence the volatility of cryptocurrency markets. The quantitative analysis employs the GARCH (Generalized Autoregressive Conditional Heteroskedasticity) model to analyze the volatility of major cryptocurrency, including Bitcoin and Ethereum, before and after the implementation of regulatory policies. Daily price data from multiple sources is analyzed, providing insights into volatility shifts corresponding to significant policy changes. The qualitative component involves a review of regulatory policy literature and semi-structured interviews with market participants, such as investors and regulators, to uncover the underlying mechanisms through which regulatory actions affect market dynamics. The results indicate that stringent regulation, such as outright bans (e.g., China), tend to increase market volatility in the short term, while regulations that promote legal integration (e.g., the EU’s MiCA framework) contribute to market stabilization over time. The study also reveals notable variations in regulatory approaches across countries, with differing impacts on global market behavior. These findings highlight the critical role of regulatory frameworks in shaping cryptocurrency market dynamics and contribute to the literature by providing both empirical evidence and policy recommendations that can inform future regulatory decision-making. By integrating qualitative insights with quantitative data, the study offers a nuanced understanding of how regulation influences cryptocurrency market volatility and stability.